Post romantic - Flenniken, Kathleen (Pacific Northwest poetry series, 2020)
"The poems in Post Romantic sort through one lifetime of moments-bits and pieces of childhood, marriage, cultural touchstones-and hold them up to the clear light. In her third book of poetry, Flenniken addresses the difficult task of learning to re-see what is before us, and trying to find comfort in a complicated world that is at once heartbreaking, confounding, and dear. The collection is bookended by two experiences of driving along the Columbia Gorge. In "November 2016," a recollection of a childhood trip and a lost generation is represented by a steady, capable-if morally complicated-American man. "Emerging Figure" follows the speaker driving the same road fifty years later when a man steps out from the dark onto the highway centerline, in effect threatening to be hit by her skidding car. His act is the embodiment of a dangerous age moving too fast.Flenniken's poems use a variety of forms, invented and traditional. Some focus on a long marriage and the redefinitions of a lifelong commitment. Family appears, past and present, foreground and background. Some poems take on nuclear history. A parallel theme is love of country, and some poems look back to childhood to trace its beginnings.The collection's structure is, like memory, associative and not chronological. In these poems, the intimate and everyday mix with the national and international-memory making all of it personal, and hindsight adding shadows to a constantly shifting past.Plume (UWP, 2012), Flenniken's award-winning second book, was a much-discussed meditation on the Hanford Nuclear Site and Flenniken's hometown of Richland, Washington. Post Romantic continues Plume's major themes of personal memory as well as national and ecological upheaval"--